HERI GUNAWAN'S POLITICAL MARKETING COMMUNICATION STRATEGY IN BUILDING ELECTABILITY IN THE BOGOR REGENCY LEGISLATIVE ELECTION - Mochamad Aroziki (PT. Media Akademik Publisher, 2025)
Legislative election competitions at the regional level require candidates to implement effective political marketing communication strategies in building voter electability. This study aims to analyze Heri Gunawan's political marketing communication strategy in building electability in the Bogor Regency legislative election. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews with candidates and campaign teams, observation of campaign activities, and documentation studies of campaign materials and media reports. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that Heri Gunawan's political marketing communication strategy is carried out in a planned and integrated manner through local issue-based message planning, adaptive voter segmentation, and the use of communication media that combines face-to-face communication and digital media. In addition, strengthening consistent and authentic political branding and the implementation of participatory two-way communication play an important role in building trust and emotional closeness with voters. The strategy contributes significantly to the formation of electability through increasing public recognition, liking, and trust in candidates. This research makes a theoretical contribution to the study of political marketing communication by emphasizing the importance of contextual and relational approaches in regional legislative elections.